2016
DOI: 10.1245/s10434-016-5236-x
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Node Mapping in Cervical and Endometrial Cancer: Indocyanine Green Versus Other Conventional Dyes—A Meta-Analysis

Abstract: In cervical and endometrial cancer, ICG SLN mapping seems to be equivalent to the combination of blue dyes and (99)TC in terms of overall and bilateral detection rates. Its safety profile and ease of use may favor its employment respect to conventional tracers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(112 citation statements)
references
References 26 publications
2
105
0
5
Order By: Relevance
“…SLN biopsy without pelvic lymphadenectomy is considered safe in cervical cancer patients with negative SLNs 35,36. Several studies have found that indocyanine green SLN mapping in cervical cancer provided higher overall and bilateral detection rates compared with current standard of care3739 and removed up to three SLNs which may be enough to accurately assess the lymph node staging in cervical cancer patients 40. The current National Comprehensive Cancer Network guidelines recommended the SLN technique for early stage cervical cancer with tumor size <2 cm 41.…”
Section: Discussionmentioning
confidence: 99%
“…SLN biopsy without pelvic lymphadenectomy is considered safe in cervical cancer patients with negative SLNs 35,36. Several studies have found that indocyanine green SLN mapping in cervical cancer provided higher overall and bilateral detection rates compared with current standard of care3739 and removed up to three SLNs which may be enough to accurately assess the lymph node staging in cervical cancer patients 40. The current National Comprehensive Cancer Network guidelines recommended the SLN technique for early stage cervical cancer with tumor size <2 cm 41.…”
Section: Discussionmentioning
confidence: 99%
“…Overall ICG remains a very safe product that performs better than the other conventional tracers (such as Tc-99m and blue dyes alone or in combination) when adopted for the SLN mapping in gynecologic oncology [2][3][4][5][6]8]. Although adverse reactions resulting from an intravenous or an interstitial injection of ICG are expected to be the same, since ICG has only been approved by FDA for intravenous injection, it is crucial to inform the patients undergoing SLN mapping on its off-label use as adverse reactions may otherwise lead to unpleasant medico-legal consequences.…”
Section: Discussionmentioning
confidence: 99%
“…This allows for an easy identification of the SLN. In gynecologic oncology this tracer has proven to be at least equivalent to the combination of technetium-99m Tc-99m and blue dyes as far as detection rates goes [2][3][4][5][6]. ICG seems to perform better in obese patients and is user friendlier as it does not require a preoperative intracervical injection as is the case with Tc-99m.…”
Section: Introductionmentioning
confidence: 99%
“…Ошибки при срочном гистологическом исследовании весьма веро-ятны и не дают четкости для выбора тактики лечения и объема операции [37,38]. Результаты, полученные P. Morice с соавт., показали, что у больных РШМ могут встречаться изолированные метастазы в парааорталь-ных лимфатических узлах при отсутствии метастазов в группах наружных, общих и обтураторных тазовых коллекторов [39].…”
Section: обзорные статьиunclassified